2018
DOI: 10.22146/jp.32363
|View full text |Cite
|
Sign up to set email alerts
|

Marital Status, Career and Income as Indicators of Life Satisfaction Among Middle-aged Career Women in Hulu Langat, Selangor, Malaysia

Abstract: Life satisfaction is a subjective construct that varies according to gender, education level, age, income, marital status, and other demographic factors. Life satisfaction is an important issue among middle-aged women. They face various responsibilities, roles and expectation at this age. The objective of this article is to identify the differences in life satisfaction among middleaged Malay women from different educational level, marital status, career and income. This study applied a survey technique, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 18 publications
(25 reference statements)
0
1
1
Order By: Relevance
“…In present study statistically significant relationship was found between life satisfaction and marital status. Score was highest in single person these results were contrary to researches done by Zakaria et al which showed ore life satisfaction with being married (p-value <0.05), 19 the difference might be due to marital status affecting their life decisions and positions. Our study showed statistically significant relationship between un employment and life satisfaction score, unemployed individuals were more satisfied with their…”
Section: Discussioncontrasting
confidence: 92%
“…In present study statistically significant relationship was found between life satisfaction and marital status. Score was highest in single person these results were contrary to researches done by Zakaria et al which showed ore life satisfaction with being married (p-value <0.05), 19 the difference might be due to marital status affecting their life decisions and positions. Our study showed statistically significant relationship between un employment and life satisfaction score, unemployed individuals were more satisfied with their…”
Section: Discussioncontrasting
confidence: 92%
“…This shows that Malaysia emphasizes the importance of attain education for better economic stability. From here, having good income and good education background provide securities to achieve better life satisfaction faced by working women (Marziah et al, 2018;Marziah et al, 2017). There is also the influence of marital status, especially married status, that contribute to safety especially among females that live in rural areas (Kohno et al, 2020).…”
Section: Socio-demographics In Theoretical Frameworkmentioning
confidence: 99%
“…Feeling safe is obtained when individuals achieve securities and free from feeling fear and anxieties (Hayre-Kwan et al, 2021;McLeod, 2020;Taormina et al, 2013;Waltemire et al, 2020). In this world today, when related to working women, they desire to gain good and stable income in career they pursue in, which contributes to high level of life satisfaction (Marziah et al, 2018). In addition, educational attainment among working women also have increased Salleh et al (2022) to reduce income gaps (Parvazian et al, 2017).…”
Section: Socio-demographics In Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies on marital satisfaction in Malaysia focus on variables other than spiritual well-being and religiosity. For example, emotional intelligence (Hoesni et al, 2018), general happiness (Hoesni & Zakaria, 2019), quality of life (Ismail, Azlan & Yusof 2015), psychological disorders (Wan Azlan et al, 2018), love (Hoesni et al, 2016), demographics, for example, marital status, career and income (Zakaria, Abdul Kadir & Baharudin 2017), gender (Hoesni et al, 2013), job satisfaction and performance at work (Nasir & Amin 2010), personality traits and the risk of divorce (Bahareh et al, 2013), anxiety in communicating (Hoesni, Manap, & Zakaria, 2020) and positive communication in marriage (Hoesni, Manap, & Zakaria, 2017). As a result, more studies delving into the aspects of spirituality and marriage are needed to understand the psychology of marriage in the Malaysian context.…”
Section: Introductionmentioning
confidence: 99%